Determinants Of High Rate Of Inflation In Iran - Zinatbakhsh, Amirabbas (2009)
The purpose of this research study is to find out the determinants of high rate of inflation in Islamic Republic of Iran. This research study tries to examine the relationship among macro economical variables such as Gross Domestic Products, Exchange rate, Money supply, Import Prices Index, and Inflation rate in Iran